EFEKTIFITAS IKLAN SUBLIMINAL OPPO DALAM ACARA INI TALKSHOW TERHADAP KONSUMEN DI WARUNG KOPI TRANSIT BANDA ACEH - Muhammad Ichsan; Alamsyah Taher (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRAK -Penelitian ini berjudul Efektivitas Iklan Subliminal Oppo Dalam Program televisi “Ini Talkshow” Terhadap Konsumen Di Warung Kopi Transit Banda Aceh. Tujuan penelitianini untuk mengetahui efektivitas iklan subliminal oppo terhadap konsumen program televisi “ini talkshow”. Pendekatan yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Subjek penelitian yang menjadi informan adalah sebanyak 6 orang terdiri dari seluruh pengunjung warung kopi transit di Banda Aceh. Teknik pengumpulan data yang digunakan ialah wawancara dan studi dokumen serta studi pada observasi. Teori yang digunakan dalampenelitianiniadalah teori jarum suntik dan dengan menggunakan AIDDA Model ( teori iklan). Hasil penelitian menunjukkan bahwa Acara ini talkshow di net. Tv adalah sebuah acara yang yang sudah digemari oleh oleh masyarakat indonesia dan tidak heran juga banyak yang menyukai program seperti ini talkshow, bagi penonton tersebut mereka mengetahui adanya iklan oppo dalam dalam acara ini talkshow. Perasaan yang timbul bagi konsumen setelah melihat iklan dari program ini talkshow di Net.tv adalah rasa ketertarikan terhadap produk tersebut, tahapan ini disebut interest. Sehingga timbul keinginan untuk membeli produk itu, tahapan ini disebut desire.  dan pada tahapan selanjutnya konsumen ingin benar-benar membeli produk tersebut, tahapan ini disebut juga dengan desicion. Setelah semuanya terpenuhi oleh calon pembeli konsumen melakukan tindakan pembelian tersebut terhadap iklan yang ditayangkan. Subliminal Oppo Advertising Effectiveness In TV Program "This Talkshow" Against Consumers In Banda Aceh Transit Coffee Shop. ABSTRACT – This research is titled Subliminal Oppo Advertising Effectiveness In TV Program "This Talkshow" Against Consumers In Banda Aceh Transit Coffee Shop. The purpose of this research is to know the effectiveness of subliminal oppo advertisement to consumer of television program "this talk show". The approach used in this research is descriptive qualitative method. Research subjects who become informants is as much as 6 people consisting of all visitors to the coffee shop transit in Banda Aceh. Data collection techniques used are interviews and document studies and studies on observation. The theory used in this research is the theory of syringes and by using AIDDA Model (ad theory). The results show that this event talkshow on the net. Tv is an event that has been favored by the Indonesian community and not surprisingly also many who like this program talkshow, for the audience they know the existence of oppo ads in this talk show. The feeling that arises for the consumer after seeing the advertisement of this program talkshow on Net.tv is a sense of interest in the product, this stage is called interest. So arises the desire to buy the product, this stage is called desire. and in the next stage consumers want to actually buy the product, this stage is also called the desicion. Once everything is met by the prospective buyer the consumer takes the purchase action against the advertisement that is served  ABSTRACT – This research is titled Subliminal Oppo Advertising Effectiveness In TV Program "This Talkshow" Against Consumers In Banda Aceh Transit Coffee Shop. The purpose of this research is to know the effectiveness of subliminal oppo advertisement to consumer of television program "this talk show". The approach used in this research is descriptive qualitative method. Research subjects who become informants is as much as 6 people consisting of all visitors to the coffee shop transit in Banda Aceh. Data collection techniques used are interviews and document studies and studies on observation. The theory used in this research is the theory of syringes and by using AIDDA Model (ad theory). The results show that this event talkshow on the net. Tv is an event that has been favored by the Indonesian community and not surprisingly also many who like this program talkshow, for the audience they know the existence of oppo ads in this talk show. The feeling that arises for the consumer after seeing the advertisement of this program talkshow on Net.tv is a sense of interest in the product, this stage is called interest. So arises the desire to buy the product, this stage is called desire. and in the next stage consumers want to actually buy the product, this stage is also called the desicion. Once everything is met by the prospective buyer the consumer takes the purchase action against the advertisement that is served